2010
DOI: 10.1098/rsif.2010.0428
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-responsive liquids for encapsulation storage and controlled release of drugs from nano-shell capsules

Abstract: Drug-delivery systems with a unique capability to respond to a given stimulus can improve therapeutic efficacy. However, development of such systems is currently heavily reliant on responsive polymeric materials and pursuing this singular strategy limits the potential for clinical translation. In this report, with a model system used for drug-release studies, we demonstrate a new strategy: how a temperatureresponsive non-toxic, volatile liquid can be encapsulated and stored under ambient conditions and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In this regard, electrohydrodynamic (EHD) processing is a promising technique for producing particles (electrospraying) and fibers (electrospinning) from a wide range of materials such as biocompatible polymers and hydrogels, proteins and peptides [20][21][22][23][24]. EHD processing can produce uniform solid and encapsulated particles and fibers with diameters ranging from a few nanometers to several micrometers in a single step, under ambient conditions, low cost and without the need for high concentrations of additives or surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, electrohydrodynamic (EHD) processing is a promising technique for producing particles (electrospraying) and fibers (electrospinning) from a wide range of materials such as biocompatible polymers and hydrogels, proteins and peptides [20][21][22][23][24]. EHD processing can produce uniform solid and encapsulated particles and fibers with diameters ranging from a few nanometers to several micrometers in a single step, under ambient conditions, low cost and without the need for high concentrations of additives or surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…However, the major disadvantages of A microspheres is their low loading efficiency and also rapid release of proteins owing to the meshlike networks of the gel [18]. Previous studies have shown that a core-shell structure in drug -protein carriers can overcome the issues of limited loading efficiencies and rapid release of drug or protein [19][20][21]. We therefore hypothesized that introducing a core-shell structure into the A microspheres could solve the shortcomings of the pure A.…”
Section: Introductionmentioning
confidence: 99%
“…Although many research articles have been published in recent years 7,21,26,34,35 , CEHD processing is a relatively new method and thus, they are still many parameters that need to be investigated. In this work the goal was to use a two needle co-axial system with adjustable needle axial position to study how the displacement between the two needle tips affects the main characteristics and morphology of the core-shell particles and fibres produced.…”
Section: Introductionmentioning
confidence: 99%